2001
DOI: 10.1177/000992280104000905
|View full text |Cite
|
Sign up to set email alerts
|

Thrush in the Breastfeeding Dyad: Results of a Survey on Diagnosis and Treatment

Abstract: Infection with Candida albicans in the breastfeeding dyad has been associated with extreme pain in the breastfeeding mother and may lead to premature weaning. There is presently a dearth of information on diagnosis, natural history, and treatment of this condition in the literature. Therefore, before such a trial was conducted, a survey was sent to experts in the field of lactation, the members of The Academy of Breastfeeding Medicine, on the diagnosis and treatment of thrush in the breastfeeding mother and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 9 publications
0
35
0
3
Order By: Relevance
“…37 Embora não haja informações sobre a excreção da nistatina no leite materno, a maioria dos autores considera aceitável o seu uso em lactantes, uma vez que é praticamente indetetável no plasma materno após a sua ingestão. 38,39 Opções de segunda linha em infeções fúngicas superficiais durante a gestação incluem o clotrimazol e o ciclopirox, que não mostraram potencial embriotóxico em modelos animais, mas dispõem de menor evidência científica da sua utilização em mulheres grávidas (categoria de risco B pela FDA). 33,40 A absorção transcutânea para a circulação sistémica do clotrimazol e do ciclopirox são mínimas, sendo por isso improvável que afetem o lactente.…”
Section: Antifúngicos Tópicos (Categorias De Risco A/b/c Pela Fda)unclassified
“…37 Embora não haja informações sobre a excreção da nistatina no leite materno, a maioria dos autores considera aceitável o seu uso em lactantes, uma vez que é praticamente indetetável no plasma materno após a sua ingestão. 38,39 Opções de segunda linha em infeções fúngicas superficiais durante a gestação incluem o clotrimazol e o ciclopirox, que não mostraram potencial embriotóxico em modelos animais, mas dispõem de menor evidência científica da sua utilização em mulheres grávidas (categoria de risco B pela FDA). 33,40 A absorção transcutânea para a circulação sistémica do clotrimazol e do ciclopirox são mínimas, sendo por isso improvável que afetem o lactente.…”
Section: Antifúngicos Tópicos (Categorias De Risco A/b/c Pela Fda)unclassified
“…A levedura mais comumente isolada em nosso estudo foi a C. albicans. Quando este patógeno infecta mães lactantes, o ato de amamentar se torna extremamente doloroso, o que pode levar a um desmame prematuro (6) .…”
Section: Perfi L E Valores De Pz De Candida Albicans Isoladas De Lactunclassified
“…Em estudo realizado por Brent (6) , o tratamento mais comum da candidíase mamária foi nistatina creme para a mãe e nistatina oral para o bebê. Segundo Bodley et al (5) , a candidíase mamária pode apresentar uma refratariedade ao tratamento com nistatina creme, sendo necessário o uso de fluconazol oral.…”
Section: Perfi L E Valores De Pz De Candida Albicans Isoladas De Lactunclassified
“…Superficial and localized breast yeast infections (mammary candidosis) in lactating women have been reported (1,2). The diagnosis and management of candidosis in the breastfeeding mother and infant are challenging (5). Mammary candidosis is most often presumptively diagnosed by signs or symptoms such as burning or shooting pain in the breast during and after feedings and persistently sore or cracked nipples that do not heal (11).…”
mentioning
confidence: 99%
“…Mammary candidosis is most often presumptively diagnosed by signs or symptoms such as burning or shooting pain in the breast during and after feedings and persistently sore or cracked nipples that do not heal (11). In a recent survey of 312 physicians in the Academy of Breastfeeding Medicine, 95% of family practitioners and 87% of obstetricians/gynecologists did not use laboratory tests to diagnose mammary candidosis (5). However, diagnosis of mammary candidosis based on symptoms alone may be erroneous, as it has been shown that breast pain is frequently associated with Staphylococcus aureus infection among breastfeeding women (1,12).…”
mentioning
confidence: 99%